Notary’s Liability for the Cancellation of the Deed of Establishment of A Foreign Investment Limited Liability Company due to Violation of the Notary Profession - Ayu Zihan Nabillah (Authentica, 2023)
AbstractThe need for notary services, especially in terms of the preparation of deeds of establishment of limited liability companies is increasing, along with the rapid development of the business world, which is also supported by the development of information technology. The establishment of a limited liability company according to Article 7 paragraph (1) and paragraph (2) of the Limited Liability Company Law, is based on an agreement between 2 (two) or more persons, by obliging each founder to take a share and stated before a Notary in a deed of establishment in Indonesian language containing the company's articles of association. In addition to requiring a deed of establishment, the establishment of a limited liability company also requires capital. The capital can come from domestic or foreign/foreign sources. Therefore, the type of limited liability company based on the type of capital is divided into 2 (two), namely Domestic Capital Limited Liability Company (PMDN) and Foreign Capital Limited Liability Company (PMA). The type of research in this legal research is normative or doctrinal legal research conducted by examining secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. In practice, problems sometimes arise, especially in Limited Liability Foreign Capital Companies (PMA), as in the case decided by the Denpasar District Court Decision Number: 485/Pdt.G/2015/PN.Dps. The Panel of Judges of the Denpasar District Court decided that Deed No. 52 concerning the Establishment of PT Mexicano Asia made before Notary I Putu Chandra, S.H., was declared null and void.Keywords: deed cancellation, notary; limited liability company establishment; foreign investment.